Welfare compensation for unemployment in the great recession - Mari\~na Fernandez-Salgado; Francesco Figari; Holly Sutherland; Alberto Tumino (University of Essex, Institute for Social and Economic Research (ISER), 2012)
This paper analyses the extent to which tax-benefit systems provide an automatic stabilisation of income for those who became unemployed at the onset of the Great Recession. The focus of the analysis is on the compensation for earnings lost due to unemployment which is channelled through the welfare systems to this group of people who are clearly vulnerable to the recession's adverse effects. In order to assess the impact of unemployment on household income, counterfactual scenarios are simulated by using EUROMOD, the EU-wide microsimulation model, integrated with information from the EU-LFS data. This paper provides evidence on the differing degrees of relative and absolute resilience of the household incomes of the new unemployed. These arise from the variations in the protection offered by the national tax-benefit systems, depending on entitlement or not to Unemployment Benefits, and from the personal and household circumstances of those most recently at risk of unemployment in the countries considered.
Keywords: C81; H55; I3; 330; unemployment; European Union; household income; microsimulation